STRATEGI NATION BRANDING THAILAND MELALUI AMAZING THAILAND DALAM MEMPROMOSIKAN PARIWISATA NASIONAL DI SINGAPURA (2019-2023) - Febryani, Felly; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research will analyse and describe the nation branding strategy through initiatives undertaken by the Thai government in branding the country through Amazing Thailand as a tourism campaign, especially in promoting the national tourism industry in Singapore. Seeing that in a certain period of time there was a decline in Singaporean tourist visits to Thailand. The Amazing Thailand campaign is an effort to re-enhance Thailand's image to Singaporeans who want to visit Thailand. This research uses a pluralism perspective and is analysed based on the theory and concept of nation branding by Keith Dinnie through his book entitled "Nation Branding, Concepts, Issues, Practice". The research method used in this research is a qualitative method with literature study data collection techniques to collect and analyze data from secondary sources obtained from books, articles, journals and other forms related to the problems studied. The results showed that Thailand has conducted a nation branding strategy through Amazing Thailand in promoting national tourism through programs such as Amazing Thailand Travel Confidently with Grab and several roadshows in Singapore such as Amazing Thailand Craft your Journey 2023 and Amazing Thailand Krabi Roadshow to Singapore 2023 in promoting Thai tourism. The campaign was successful in re-establishing Thailand's image in Singapore with an increase in Singaporean tourist arrivals to Thailand. Keywords: Amazing Thailand, Nation Branding, Tourism, Thailand, Singapore